Kata Serapan Bahasa Arab Pada Teks Pidato Kenegaraan Presiden RI - Fahmi, Alif Anharul; Nashihah, Durrotun; Muthoharoh, Imroatul; Mustofa, Syaiful (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The vocabulary of the Indonesian language has absorbed many words from foreign languages, one of which is Arabic. This vocabulary is spread across various aspects of Indonesian society. This research aims to understand the absorption of Arabic vocabulary into the Indonesian language in the state speeches of the President of the Republic of Indonesia, Ir. Joko Widodo, during the annual session of the People's Consultative Assembly (MPR). The researcher employs a qualitative approach with a content analysis methodology. Data collection involves the use of documents, with the primary data source being the state speeches of the President of RI during the annual MPR sessions from 2020 to 2023. Data analysis follows Miles and Huberman's theory, including data presentation, data reduction, and drawing conclusions. Data validation is conducted through triangulation. The research findings indicate that the absorption of Arabic vocabulary into the Indonesian language in the state speeches of President RI Ir. Joko Widodo during the annual MPR sessions from 2020 to 2023 includes 79 loanwords. These consist of 22 words with similar sounds, 21 words with dissimilation, 6 words with metathesis, 1 word with diphthongization, and 15 words with anaptyxis. Meanwhile, zeroization includes 15 words, comprising 6 words with apheresis, 5 words with syncope, and 4 words with apocope. Abstrak Kosakata bahasa Indonesia banyak menyerap dari bahasa asing, salah satunya adalah bahasa Arab. Kosakata tersebut tersebar di seluruh aspek kehidupan masayarakat Indonesia. Penelitian ini bertujuan untuk mengetahui penyerapan kosakata bahasa Arab menjadi bahasa Indonesia pada pidato kenegaraan Presiden Republik Indonesia Ir. Joko Widodo dalam sidang tahunan MPR. Peneliti menggunakan pendekatan kualitatif dengan metode analisis konten. Teknik pengumpulan data menggunakan dokumen. Sumber data penelitian ini berupa teks pidato kenegaraan Presiden RI dalam sidang tahunan MPR pada tahun 2020-2023. Analisis data penelitian menggunakan teori Miles dan Huberman yaitu penyajian data, reduksi data, dan penarikan kesimpulan. Validasi data menggunakan triangulasi. Hasil penelitian ini menunjukkan bahwa penyerapan kosakata bahasa Arab menjadi bahasa Indonesia pada teks pidato kenegaraan Presiden RI Ir. Joko Widodo dalam sidang tahunan MPR pada tahun 2020-2023 terdapat 79 kata serapan. Yaitu meliputi 22 kata serapan dengan bunyi yang sama, 21 kata desimilasi, 6 kata metatesis, 1 kata diftongisasi, dan 15 kata anaptiksis. Sedangkan pada zeroisasi terdapat 15 kata, dengan rincian 6 kata apheresis, 5 kata sinkop, dan 4 kata apokop.